The Role Of Body image In Determining The Nutrional Status Of Adolecent Girls In Padang Panjang - Riva Muharramah; Kasmita Kasmita; Yuliana Yuliana; Lucy Fridayati (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
Appearance and body shape often become a primary concern, especially for adolescent girls during puberty. However, a distorted body image can affect a person's nutritional status. Even adolescent girls with a tendency toward being underweight are at risk of suffering from certain diseases that impact the occurrence of stunting. The purpose of this study is to determine the extent of the influence of body image on the nutritional status of adolescent girls in Padang Panjang City. This study is quantitative with a survey method involving a sample of 285 adolescent girls from high schools (SMA) and vocational high schools (SMK) in Padang Panjang City. The sampling technique used was proportional random sampling. The instruments employed were the Body Shape Questionnaire (BSQ-34), consisting of 34 questions with a 6-point Likert scale, and nutritional status was measured using the Body Mass Index (BMI). Data analysis techniques included descriptive analysis, normality test, homogeneity test, linearity test, and simple linear regression. The results showed that 62.8% of respondents had a positive body image, while 37.2% had a negative body image. The average nutritional status in Padang Panjang City was normal at 62.8%. The hypothesis test results showed an R² value of 0.244 (24.4%), meaning that the more positive a person's body image, the better their nutritional status. Nutritional status in Padang Panjang City is influenced by body image by 24.4%, while 75.6% is affected by other factors not examined in this study.